ACTUAL PROBLEMS OF IMPROVING THE PHYSICAL FITNESS OF STUDENTS, PROFESSIONAL AND APPLIED PHYSICAL TRAINING (Web of Teachers: Inderscience Research, 2024)
The question was raised about the actual problems of improving the physical fitness of student youth, where the main problems and solutions were identified. The main needs in physical culture are described. Ways of perfection of physical culture are offered.